Time Monitoring System for Assembly Line Operators Using RFID - Hassan, Maisarah; Muhammad Razif, Muhammad Rusydi (International Journal of Integrated Engineering, 2023)
This project discussed monitoring system in an assembly line to monitor and track the performance of the operators in industries. Industry is an important workplace around the world including research and development, design, process, production, quality assurance and so on. A large number of jobs involve humans, and there are also parts that require humans to work using machines, especially operational workers or operators. There are many systems developed in the industry that involve the operator, some of them are to monitor the machining process, and some are to monitor and control the machine. Assembly line operator performance is a critical aspect that severely affects the overall production performance in any production nature. Non-productive time contributes to inequality in task distribution that often results in bottleneck points on a production line. Therefore, the non-productive time is considered as a waste of resources that has a relative impact on the production yield of an industry. In this project, Radio Frequency Identification (RFID) is used on the production line as a monitoring system so that it can help organizations to increase the performance of the working environment among all the employees as well as to achieve better production yield by reducing the non-productive time of assembly line operator.